Legal Aspects of Unmanned Warfare and Military Drone Operations - Kowalczewska, Kaja (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
The evolving landscape of warfare has been transformed by the technological advancement of unmanned platforms. The use of drones has facilitated the remote execution of military operations, allowing armed conflict to achieve a global and presumably selective scope through sophisticated technological organisation. Nevertheless, the past two decades of mainly American practices have revealed that so-called “precision warfare” poses novel ethical and legal challenges. Despite the multifaceted roles played by contemporary military robots, especially in scenarios where they replace human combatants and execute lethal actions, comprehensive legal scrutiny is imperative. Although unmanned platforms do not attain the same level of autonomy as military systems enabled by artificial intelligence, they still present challenges. In the case of unmanned platforms, the contentious aspects predominantly relate to their methods of employment rather than the inherent illegality of this means of warfare. This chapter critically dissects the legal complexities surrounding these technological innovations, distinguishing drones from autonomous weapons and examining their deployment methods and the relevant legal framework. Key issues include the necessity for legal review of weapons before deployment, the use of unmanned platforms beyond the theatre of active armed conflict, and contentious combat methods such as targeted killings and signature strikes. While predominant discussions centre on U.S. drone warfare, this chapter incorporates a European perspective where relevant, highlighting the need for harmonisation of democratic standards. Keywords: unmanned platforms, drone warfare, use of force, law of armed conflict, international human rights law, drone policy